2008
DOI: 10.1152/ajpregu.00829.2007
|View full text |Cite|
|
Sign up to set email alerts
|

Circadian rhythm disorganization produces profound cardiovascular and renal disease in hamsters

Abstract: Sleep deprivation, shift work, and jet lag all disrupt normal biological rhythms and have major impacts on health; however, circadian disorganization has never been shown as a causal risk factor in organ disease. We now demonstrate devastating effects of rhythm disorganization on cardiovascular and renal integrity and that interventions based on circadian principles prevent disease pathology caused by a short-period mutation (tau) of the circadian system in hamsters. The point mutation in the circadian regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
210
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(221 citation statements)
references
References 26 publications
7
210
3
1
Order By: Relevance
“…In contrast to the tau mutation, the Per2 Brdm1 mutation does not strongly affect the circadian period and had a negligible effect on activity patterns in outdoor conditions (14). We cannot exclude the possibility that the effects we report for the tau mutation may be due to an unknown noncircadian pleiotropic effect, even though the earlier laboratory studies on tau mutant hamsters have clearly revealed health consequences as a result of the deleterious impact of inappropriate entrainment to artificial lighting regimes (17).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast to the tau mutation, the Per2 Brdm1 mutation does not strongly affect the circadian period and had a negligible effect on activity patterns in outdoor conditions (14). We cannot exclude the possibility that the effects we report for the tau mutation may be due to an unknown noncircadian pleiotropic effect, even though the earlier laboratory studies on tau mutant hamsters have clearly revealed health consequences as a result of the deleterious impact of inappropriate entrainment to artificial lighting regimes (17).…”
Section: Discussioncontrasting
confidence: 57%
“…In another study, heterozygote tau mutant hamsters (expressing a free-running 22-h circadian period in absence of time cues) were kept on a 24-h LD cycle, to which these animals entrained with fractured activity patterns and earlier onset of activity. This aberrant rhythmicity in the 24-h LD cycle was associated with cardiac defects, which did not arise in heterozygotes kept on a 22-h LD cycle (16,17). The effects were also not observed after ablation of the central circadian pacemaker in the hypothalamus (suprachiasmatic nucleus) or in homozygous hamsters, which do not entrain to modulo-24, and free run across such lighting regimes.…”
Section: Discussionmentioning
confidence: 89%
“…Circadian rhythms and the core clock factors CLOCK and BMAL1 have been implicated in a growing number of systemic pathologies, including metabolic disease, aging, and cardiovascular disease (16)(17)(18). To date, however, no genetic studies have examined what role circadian rhythms play in adult skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse cardiac events show significant diurnal variations (82), and mortality is higher for people whose professions expose them to frequent disruption of the biorhythm (e.g., flight crews, shift workers) (83). A recent animal experiment showed that in the long run, disruption of the biorhythm by genetic manipulation caused target organ damage in kidney and heart (84). Against this background, the findings of the observational DOPPS are remarkable that self-reported disturbed sleep is a powerful predictor of mortality (85), most tightly related to pain, pruritus, and depression.…”
Section: Disrupted Biorhythmmentioning
confidence: 99%